A case of aortic valve leaflet tear and perforations after neocuspidization. (18th February 2019) - Makino, Masato; Yamamoto, Hiroyuki; Ishibashi‐Ueda, Hatsue; Nakamura, Yoshitsugu
Abstract: Although aortic valve (AV) replacement is a curative procedure for severe aortic stenosis, prosthetic heart valves have many disadvantages and cause serious complications. A new promising surgical procedure—aortic valve neocuspidization (AVNeo)—has recently been developed; it is an original method of AV reconstruction with autologous pericardium. It has been reported to yield excellent medium‐term results with respect to durability and complications. Herein, we encountered a first case of AV leaflet tear and perforations 27 months after AVNeo using autologous pericardium. AV leaflet tear or perforation is well recognized as a long‐term serious complication of pericardial xenografts. Interestingly, however, AVNeo caused early structural valve deterioration in the current case. In the present case, an eccentric aortic regurgitation jet observed on colour flow imaging led us to reach the correct diagnosis. Finally, the patient showed complete recovery with redo AV replacement. This case highlights the importance of understanding the potential pitfalls of this new surgical technique and that of colour Doppler echocardiography in reaching a definite diagnosis.